After Stonewall - Scagliotti, John (United States, 1999)
Soros Documentary Fund On June 27, 1969, in what is considered the birth of the modern gay civil rights movement, the homosexual, bisexual and transgender patrons of the Stonewall Bar in New York City spontaneously united and fought back against chronic police harassment, jeers and arrests. A sequel to "Before Stonewall", the film chronicles the gay and lesbian experience since the Stonewall riots to the end of the 20th century. The film captures the struggles, defeats and triumphs of a proud, though still stigmatized, community and records the personal accounts of gays and lesbians who have transformed not only their own lives, but also American society and the world community.